Novel dihydroartemisinin derivatives exhibiting anticancer and antimalarial activities - Anh, Le Duc; Hung, Truong Ngoc; Ha, Ninh Duc; Inh, Cam Thi; Dan, Nguyen Trong; Thinh, Nguyen Van; Tien, Le Quang; Anh, Cao Quoc; Chinh, Luu Van (Vietnam Journal of Science and Technology, 2026)
A two-step procedure was used for the synthesis of six novel derivatives of artemisinin, a main active sesquiterpene lactone, which could be easily isolated on a large scale from the traditional medicinal plant Artemisia annua L in Vietnam. Structures of the prepared derivatives were characterized by full-length data of spectra, including 1H-, 13C-NMR and HRMS. Screening for their in vitro cytotoxic activity was performed together with dihydroartemisinin (DHA) against three human cancer cell lines: HepG2, A549, and HeLa. Additionally, these derivatives were evaluated for antimalarial activity against P. plasmodium using the chloroquine-resistant strain (K1) and the chloroquine-sensitive strain (T96). The results showed that the prepared derivatives exhibited the cytotoxic activity against HepG2, LU-1, and HeLa cells with IC50 values ranging from 1.32-18.38 µg/mL, which were stronger than that of DHA. Moreover, the anti-malarial results were promising for the development of new anti-malarial drugs.